Literary representations of the Palestine/Israel conflict after the second Intifada - Curthoys, Ned; Hesse, Isabelle; Bayeh, Jumana; Bernard, Anna; Cheurfa, Hiyem; Hasabelnaby, Magda; Kaspi, Niva; Mahmoud, Radwa R.; Martin, Lowry; Punia, Aarushi; Sakr, Rita; Valassopoulos, Anastasia; et al. (Edinburgh : Edinburgh University Press, 2022)
Studies literary representations of Israel and Palestine that challenge mainstream political and historical discoursesProvides a comprehensive and up-to-date survey of the spectrum of emergent and existing literary forms that now represents the Palestine/Israel conflict to a global audienceBrings together a geographically diverse team of literary and cultural studies researchers with depth of expertise in Palestine/Israel and Middle Eastern studiesArgues that emergent literary forms have adapted to imperatives for political witnessing while offering scope for the refashioning of identity beyond restrictive nationalismsDiscusses diverse literary works from Israel, the Palestinian Occupied Territories including Gaza, as well as Belgium, Canada, Egypt, France, Lebanon, the United Kingdom and the United StatesThis edited collection brings together discussions of literary works from Israel, the Occupied Palestinian Territories, the Palestinian and Jewish Diasporas, as well as from authors and creators not directly involved with the conflict who are seeking to unpack its complexities for a wider audience. It offers new perspectives into how the Palestine/Israel conflict is, and can be, represented after the Second Palestinian Intifada, an epochal event for both Israelis and Palestinians. This collection foregrounds the thematic concerns that link literary engagements with Palestine/Israel across the globe but also examines the role that aesthetic representation plays in framing the conflict and its power dynamics. It addresses how emergent forms of writing and representation illuminate but also redescribe conflict in the context of Israel and Palestine and how, as in the case of the investigative graphic novel for example, depicting this conflict has had reverberations for representing conflict and conflict zones more widely.
The severed limb : relational life writing against technobiopolitical violence in Atef Abu Saif's The drone eats with me -- ‡t Daily encounters : diary writing and the politics of the mundane in occupied Palestine -- ‡t American Palestinian women as public intellectuals : new narratives of resistance -- ‡t The Palestinian rebel : liberty and statehood in literature -- ‡t The Israeli/Palestinian conflict in To the end of the land : some thoughts on David Grossman's Hebrew in translation -- ‡t 'Public confession' in Palestinian literary self-narratives after the second Intifada -- ‡t Detectives in Bethlehem : crime fiction in the occupied territories -- ‡t Reframing occupation after the second Intifada : drawing from experience in Francophone graphic novels -- ‡t Coming of age in graphic novels representing the Palestine/Israel conflict -- ‡t The Palestine/Israel conflict in the young adult Anglophone bildungsroman -- ‡t Feeding words with sugar : resurrecting Palestine in children's picture books from Egypt.
Online resource; title from PDF title page (publisher's Web site, viewed 30. Aug 2022).
eBooks on EBSCOhost
Keywords: Arab-Israeli conflict -- Literature and the conflict; Al-Aqsa Intifada, 2000-2005.; Conflit israélo-arabe -- Littérature et conflit; Intifada d'Al-Aqsa, 2000-2005.; HISTORY -- Middle East -- Israel & Palestine; LITERARY CRITICISM / American / General; Arab-Israeli conflict -- Literature and the conflict; Since 2000